Stark deceleration and reactivity of polyatomic molecules and ions at low temperatures - Harper, LD (2013)
This thesis describes the development of a new experimental technique for studying tunable-collision-energy, quantum state-selected, low-temperature ion-molecule reactions. This has been achieved through the combination of a Stark decelerator for neutral dipolar molecules, and a linear Paul ion trap. The Stark deceleration process for ND3 was examined in detail, through the analysis of experimental data in combination with newly written molecular dynamics simulation programs. In order to prepare a sample of molecules appropriate for collision studies, additional beamline components were introduced after the decelerator. These components were: two hexapoles, to provide transverse focussing, maximising the molecular density; a molecular buncher, providing increased longitudinal velocity resolution; and a fast-opening shutter, to separate decelerated molecules from undecelerated molecules. The sympathetic-cooling of Xe+ ions and ND+3 ions by laser-cooled, Coulomb crystallised 40Ca+ ions with the ion trap was also studied. In particular, the stable trapping of Xe+ was demonstrated for the first time, and the experimental developments that led to this are discussed. The work in this thesis represents significant progress towards studying the reaction of tunable-energy ND3 in the |j,mk> = |1,−1> quantum state with cold Xe+ ions. Ion-molecule reactions utilising ND3 molecules electrostatically guided through the Stark decelerator were performed. It was observed that the main source of error in these experiments was in the calculation of the initial number of Xe+ ions that had been sympathetically cooled into the Coulomb crystal. The sensitivity of the crystal morphology to the number of Xe+ ions was evaluated using molecular dynamics simulations. Strategies have been developed to reduce this uncertainty in future studies. In addition to experimental work, the theory of low temperature ion-molecule reactions has been developed further. The temperature at which classical and quantum mechanical calculations diverge due to purely statistical effects has been investigated using different model intermolecular potentials, for closed-shell and open-shell species, and in the ground and rotationally excited states. From the results of these calculations, several promising candidate reactions have been suggested that might exhibit statistical quantum behaviour at experimentally achievable temperatures.